"A peculiar time in my life": making sense of illness and recovery with gynaecological cancer. Issue 1 (1st January 2017) - Phillips, Eleanor; Montague, Jane; Archer, Stephanie
ABSTRACT: Purpose: Worldwide there are nearly 1.1 million new cases of gynaecological cancer annually. In England, uterine, ovarian and cervical cancers comprize the third most common type of new cancer in women. Research with gynaecological cancer patients within 6 months of diagnosis is rare, as is data collection that is roughly contemporaneous with treatment. Our aim was to explore the experiences of women who were, at study entry, within 6 weeks of surgery or were undergoing chemotherapy or radiotherapy. Methods: An interpretative phenomenological analysis (IPA) of data from 16 women in five focus groups was conducted in the UK, exploring women's experiences of being diagnosed with and treated for gynaecological cancer. Results: Participants conceptualized their experiences temporally, from the shock of diagnosis, through their cancer treatment, to thinking about recovery. They tried to make sense of diagnosis, even with treatment being complete. In the context of the Self-Regulation Model, these women were struggling to interpret a changing and multi-faceted illness identity, and attempting to return to pre-illness levels of health. Conclusions: This study adds to this under-studied time period in cancer survivorship. The results suggest that survivors' goals may change from returning to pre-illness status to reformulating goals as survival time increases.